Strategic Human Resource Management dalam Meningkatkan Kinerja Organisasi Pendidikan Islam di Era Society 5.0 (JMPI: Jurnal Manajemen Pendidikan Islam, 2026)
The Society 5.0 era requires Islamic educational organizations to develop human resources that are adaptive, innovative, and capable of integrating technology with human-centered needs. This study aims to analyze the role of Strategic Human Resource Management (SHRM) in improving the performance of Islamic educational organizations amid these environmental changes. A qualitative approach with a literature review method was employed by analyzing and synthesizing relevant academic sources. The findings indicate that SHRM contributes to strengthening organizational capacity through the integration of human resource planning, competency development, talent management, performance management, and strategic leadership. Furthermore, improved organizational performance depends not only on individual competencies but also on the organization's ability to transform human capabilities into adaptive organizational capacities through innovation, organizational learning, and human-centered technology utilization. The study concludes that SHRM can serve as a strategic instrument for developing adaptive and sustainable Islamic educational organizations while maintaining the values and distinctive mission of Islamic education in the Society 5.0 era. Keywords: Strategic Human Resource Management; organizational performance; Islamic education; Society 5.0.